2011
DOI: 10.5194/acp-11-11447-2011
|View full text |Cite
|
Sign up to set email alerts
|

The Arctic vortex in March 2011: a dynamical perspective

Abstract: Abstract. Despite the record

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 33 publications
3
57
0
Order By: Relevance
“…This is probably because most of the previous studies focussed on the ozone behaviour in spring (e.g. Hurwitz et al, 2011;Manney et al, 2011;Sinnhuber et al, 2011;Balis et al, 2011;Arnone et al, 2012;.…”
Section: Low Arctic Ozone In January 2011mentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably because most of the previous studies focussed on the ozone behaviour in spring (e.g. Hurwitz et al, 2011;Manney et al, 2011;Sinnhuber et al, 2011;Balis et al, 2011;Arnone et al, 2012;.…”
Section: Low Arctic Ozone In January 2011mentioning
confidence: 99%
“…In winterspring 2011, anomalously large ozone loss in the Arctic stratospheric polar vortex was reported (e.g. Hurwitz et al, 2011;Manney et al, 2011;Sinnhuber et al, 2011;Balis et al, 2011;Arnone et al, 2012;Adams et al, 2012;Pommereau et al, 2013). In March 2010, however, when the Arctic stratosphere was also extensively denitrified and large chlorine activation was observed Khosrawi et al, 2011;, polar ozone was unusually high Steinbrecht et al, 2011;.…”
Section: Introductionmentioning
confidence: 99%
“…Manney et al, 2011;Sinnhuber et al, 2011;Arnone et al, 2012;Kuttippurath et al, 2012;Hommel et al, 2014). The dynamical perspective, and thus the exceptional dynamical conditions of this winter, was discussed in detail by Hurwitz et al (2011), Isaksen et al (2012, Strahan et al (2013), and Shaw and Perlwitz (2014). Although the Arctic winter 2009/2010 was one of the warmest winters on record (Dörn-brack et al, 2012), it was distinguished by an exceptionally cold stratosphere (colder than the climatological mean) from mid-December 2009 to mid-January 2010, leading to prolonged PSC formation and significant denitrification (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 shows features of the boreal stratosphere in the winter and spring of 2010. In terms of boreal ozone chemistry 2010 is a typical year (Hurwitz et al, 2011). None of the qualitative features that we have pointed out in Figs.…”
Section: Resultsmentioning
confidence: 84%
“…Furthermore, there is no boreal polar jet in the spring (had an ozone hole formed in the winter, the meridional transport barrier associated with the springtime boreal polar jet would be needed to isolate the ozonedepleted air). Hurwitz et al (2011) have shown that in the satellite era, the years 1997 and 2011 are distinguished from other years by unusually low Arctic winter/spring ozone levels. With this in mind, it is natural to investigate the Lagrangian dynamics associated with the 1997 Arctic ozone loss, and compare those dynamics to the 2011 dynamics.…”
Section: Resultsmentioning
confidence: 99%